Moral education methods for inmates at temanggung detention center - Elvina Elvina Retno Hastuti; Khoirul Anam (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2024)
This research was carried out because it was motivated by the fact that as someone who is social and social, he should behave in accordance with the applicable rules and norms. However, the fact is that there are still many people in the Temanggung area whose behavior deviates from the applicable rules and norms. This means that someone who commits a deviant act must be punished and sanctioned in detention. Therefore, at the Detention Center, moral education is also provided as an effort to raise awareness for prisoners using various methods. This research aims to determine the methods of moral education for prisoners, the challenges in providing moral education to prisoners, and solutions to the challenges in providing moral education for prisoners at Temanggung Detention Center. This research was conducted using descriptive qualitative methods, with data collection techniques in the form of observation, interviews and documentation, then presenting the results regarding moral education methods for prisoners at the Temanggung Detention Center. In implementing moral education in detention centers, the methods used are the exemplary method, khitobah method, da'wah method, muhasabah an-nasf method, habituation method, and punishment method. In providing moral education to prisoners there are several challenges, namely the diversity of prisoners' backgrounds and experiences, resistance and skepticism, the context of the prison environment, the presence of new prisoners, and repatriation to society. Solutions to face these challenges include developing relevant moral education programs, building a supportive prison environment, evaluation and adjustment, and using a restorative approach.